The Marana Community in the Hohokam World - Fish, Suzanne K.; Madsen, John H.; Fish, Paul R. (University of Arizona Press, 2022)
This account of Classic Period settlement in the Tucson Basin between A.D. 1100 and 1300 is the first comprehensive description of the organization of territory, subsistence, and society in a Hohokam community of an outlying region. Broad recovery of settlement patterns reveals in unique detail the developmental history of the Marana Community and its hierarchical structure about a central site with a platform mound. Remains of diverse agricultural technologies demonstrate the means for supporting populations of previously unrecognized size.